2017
DOI: 10.3389/fimmu.2017.00595
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 Human Immunodeficiency Virus Vaccine Trial for Cross-Profiling the Kinetics of Serum and Mucosal Antibody Responses to CN54gp140 Modulated by Two Homologous Prime-Boost Vaccine Regimens

Abstract: A key aspect to finding an efficacious human immunodeficiency virus (HIV) vaccine is the optimization of vaccine schedules that can mediate the efficient maturation of protective immune responses. In the present study, we investigated the effect of alternate booster regimens on the immune responses to a candidate HIV-1 clade C CN54gp140 envelope protein, which was coadministered with the TLR4-agonist glucopyranosyl lipid A-aqueous formulation. Twelve study participants received a common three-dose intramuscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 59 publications
(95 reference statements)
5
33
1
Order By: Relevance
“…To pursue this, we developed novel PCR (Figure S1 in Supplementary Material) and ELISA protocols and combined them in a dual approach to determine the IgG1 allotype identity (G1m3 and/or G1m1) of clinical trial participants, using both human serum and mRNA. The optimized protocol was applied to determine the IgG1 allotype identity of 14 clinical trial participants from an HIV vaccine study utilizing a Clade C gp140 envelope protein (Figure 1 ; Figure S2 in Supplementary Material) ( 21 ). IgG1-allotyping X001 study participants revealed that 3/14 (21%) were homozygous for G1m1 and 6/14 (43%) homozygous for G1m3, with 5/14 (36%) carrying both alleles (heterozygous).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To pursue this, we developed novel PCR (Figure S1 in Supplementary Material) and ELISA protocols and combined them in a dual approach to determine the IgG1 allotype identity (G1m3 and/or G1m1) of clinical trial participants, using both human serum and mRNA. The optimized protocol was applied to determine the IgG1 allotype identity of 14 clinical trial participants from an HIV vaccine study utilizing a Clade C gp140 envelope protein (Figure 1 ; Figure S2 in Supplementary Material) ( 21 ). IgG1-allotyping X001 study participants revealed that 3/14 (21%) were homozygous for G1m1 and 6/14 (43%) homozygous for G1m3, with 5/14 (36%) carrying both alleles (heterozygous).…”
Section: Resultsmentioning
confidence: 99%
“…This study mainly builds upon findings from the previously published X001 clinical trial ( 21 ), registered at under no. NCT01966900, EudraCT 2013-001032-22.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations